2018
DOI: 10.1590/1807-7692bar2018180019
|View full text |Cite
|
Sign up to set email alerts
|

Microcredit and Gender: Are There Differences in the Credit Conditions?

Abstract: By means of a distinguished approach of credit granting, microcredit programs stand out as a socioeconomic alternative for social insertion and fighting against poverty. In this context, a factor that has gained prominence in literature is the female participation in these programs. Therefore, knowing that the literature indicates that there is a lower level of default among women, and considering that gender influence over the financing value has been disproportionate, the aim of this research was to evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…It was observed that women are more likely to be committed to repaying their loans as they prefer income generating opportunities that can be carried on without interfering in their household roles whilst men prefer to have formal jobs for security. One is also led to accept this position because women have limited access to finance and microcredit is a very import source that they would not want to lose as a result of low compliance (Salgado & Aire, 2018).…”
Section: Impact Of Microcredit On Womenmentioning
confidence: 99%
“…It was observed that women are more likely to be committed to repaying their loans as they prefer income generating opportunities that can be carried on without interfering in their household roles whilst men prefer to have formal jobs for security. One is also led to accept this position because women have limited access to finance and microcredit is a very import source that they would not want to lose as a result of low compliance (Salgado & Aire, 2018).…”
Section: Impact Of Microcredit On Womenmentioning
confidence: 99%
“…Scientific studies of the theory and practice of microcredit, which in a broader sense is called microfinancing, covered different continents [2][3][4][5][6][7][8][9][10] with a focus on financial support for private agriculture, women's employment, and the development of small-scale production. A number of works by foreign and domestic scientists are devoted to consideration of theoretical and practical aspects of social banking [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…However, poor women are hindered from accessing formal banking and financial services, often due to intersects with social and cultural barriers (Kabeer, 2005b). However, poor men are more likely to have financial control and decision-making to exert power over household assets, and therefore have better collateral ability to engage in the banking systems (Salgado & Aires, 2018). Therefore, women drive the demand for microfinance and have high dependence on MFIs, which use social collateral systems to provide loans.…”
Section: Impact Of Lending To Womenmentioning
confidence: 99%